Measurements of mantle attenuation around the Yellowstone hotspot - Costa, Gladys Esther, author; Schutt, Derek L., advisor; Buchanan, Kristen S., committee member; Hannah, Judith L., committee member; Harry, Dennis L., committee member (Colorado State University. Libraries, 2011)
Estimation of the seismic attenuation t* was performed using teleseismic P-wave spectra recorded by 174 broadband seismic stations around the Yellowstone hotspot, WY, US. P-wave spectra used were generated by earthquakes with a moment magnitude (MW) greater than 6.4 and with epicentral distances ranging from 30° to 180°, with focal depths greater than 200 km, within a time frame from 1995 to 2009. Multi-channel cross-correlation was used to align all waveforms, then the futterman operator was applied to estimate the variations in t*. t* residuals vary from -0.5 to 0.5s. Most dt*/d[travel time] values were found to be in the negative domain, which contradicts expected values. This could imply that the absorption or dissipation of energy and the frequency dependence of seismic velocities are not due to intrinsic attenuation but rather due to scattering in the mantle and/or water content in the vicinity of the Yellowstone plume.